TINJAUAN KESESUAIAN LONG STORAGE KALIMATI SEBAGAI SARANA PENYIMPANAN AIR DAN DESTINASI WISATA KECAMATAN TARIK - SIDOARJO - Aurellya Abdillah Wijaya Putri; sudarti sudarti (UHN IGB Sugriwa Denpasar, 2022)
Sidoarjo Regency is an area that is growing rapidly in the field of development. The construction of the Kalisti Long Storage Reservoir is one of the strategies of the Sidoarjo district government to accommodate water which will then be used as raw material for PDAM. The Kalimati Long Storage Reservoir has an area of ​​about five square kilometers which can accommodate about 1.5 million cubic meters of water. It is located in two places, namely Sidoarjo Regency and Mojokerto Regency. Construction of a reservoir located in Tarik Village, Tarik District, Sidoarjo Regency. The purpose of this study was to determine the level of suitability of the Kalimati Long Storage as a means of storing raw water and a local tourist destination in the Tarik sub-district, Sidoarjo Regency. This study uses location survey research in Tarik Village, Tarik District, Sidoarjo Regency and also literature studies with data collection techniques by collecting several previous studies whose topics are related to the theme of this article to answer the suitability of the Kalimati Long Storage as a storage place for raw water and a local tourist destination. . Previous research that has been collected is then compiled, analyzed, and concluded. Thus, getting a conclusion regarding the suitability of the use of the Kaliati Long Storage. The conclusion in this study can be drawn that from the results of the analysis of the suitability of the Long Storage Kalimati as storage of raw water if it is calculated that it can accommodate an average water discharge of 1,500 liters per second so that the need for water supply for local residents can be met. Not only can it meet the needs of raw water, the Kalimati Long Storage has the potential and is suitable to become a local tourist destination whose landscape is arranged in an attractive manner. The suitability of sports locations such as jogging tracks has a very suitable category coupled with a view of the mountain range.